Commentary: The Moment of Truth – transcending Knowledge through Myriads of Creativity - Matrahah, Izaddin (Idealogy Journal; Vol 4 No 2 (2019): Idealogy Journal (September 2019)DO - 10.24191/idealogy.v4i2.151, 2019)
Letter to Editor - No Abstract